Mitochondrial and Oxidative Stress Response in HepG2 Cells Following Acute and Prolonged Exposure to Antiretroviral Drugs. Issue 9 (September 2015) - Nagiah, Savania; Phulukdaree, Alisa; Chuturgoon, Anil
ABSTRACT Chronic HIV treatment with antiretroviral drugs has been associated with adverse health outcomes. Mitochondrial toxicity exhibited by nucleoside reverse transcriptase inhibitors (NRTIs) is pinpointed as a molecular mechanism of toxicity. This study evaluated the effect of NRTIs: Zidovudine (AZT, 7.1 μM), Stavudine (d4T, 4 μM) and Tenofovir (TFV, 1.2 μM), on mitochondrial (mt) stress response, mtDNA integrity and oxidative stress response in human hepatoma cells at 24 and 120 h. Markers for mt function, mt biogenesis, oxidative stress parameters, and antioxidant response were evaluated by spectrophotometry, luminometry, flow cytometry, qPCR and western blots. We found that AZT and d4T reduced mtDNA integrity (120 h, AZT: 76.1%; d4T:36.1%, P < 0.05) and remained unchanged with TFV. All three NRTIs, however, reduced ATP levels (AZT: 38%; d4T: 56.4%; TFV: 27.4%, P = 0.01) and mt membrane potential at 120 h (P < 0.005). Oxidative damage and reactive oxygen species (ROS) were increased by TFV and AZT at 24 h, and by d4T at 120 h (P < 0.05). Antioxidant response molecules and mt biogenesis markers were elevated by all NRTIs, with TFV causing the most significant increase (P < 0.05). Data from this study suggest that AZT, d4T and TFV alter mt function. TFV, however, achieves this independently of mtDNA depletion. Furthermore, AZT exerts toxicity soon after exposure as noted from changes at 24 h and d4T exerts greater toxicity over prolonged exposure (120 h). J. Cell. Biochem. 116: 1939–1946, 2015. © 2015 Wiley Periodicals, Inc.